Carriage of Neisseria meningitidis in Men Who Have Sex With Men Presenting to Public Sexual Health Clinics, New York City. Issue 8 (August 2020) - Ngai, Stephanie; Weiss, Don; Bell, Julie Anne; Majrud, Difaa; Zayas, Greicy; Crawley, Addie; Kornblum, John; Rodriguez-Rivera, Lorraine D.; Quinlan, Tammy; Halse, Tanya A.; Retchless, Adam C.; MacNeil, Jessica; et al.
Abstract : Background: We conducted a Neisseria meningitidis (Nm) carriage study among men who have sex with men (MSM) to explore possible sexual transmission. Methods: We paired information on patient characteristics with oropharyngeal, rectal, and urethral Nm culture results to assess associations with Nm carriage among 706 MSM at New York City sexual health clinics. The Nm isolates were characterized by whole genome sequencing. Results: Twenty-three percent (163 of 706) of MSM were Nm carriers. Oropharyngeal carriage was 22.6% (159 of 703), rectal 0.9% (6 of 695), and urethral 0.4% (3 of 696). Oropharyngeal carriage was associated with the following recent (past 30 days) exposures: 3 or more men kissed (adjusted relative risk [aRR], 1.38; 95% confidence interval [CI], 1.03–1.86), performing oral sex (aRR, 1.81; 95% CI, 1.04–3.18), and antibiotic use (aRR, 0.33; 95% CI, 0.19–0.57). Sixteen clonal complexes were identified; 27% belonged to invasive lineages. Conclusions: Our findings suggest that oral sex and the number of recent kissing partners contribute to Nm carriage in MSM. Abstract : A Neisseria meningitidis carriage study among men who have sex with men attending sexual health clinics found low urethral and rectal levels and that recent oral sex and kissing contributed to oropharyngeal carriage.